Analisis Time Series dan Cross Section Perbandingan Kinerja Keuangan Studi Kasus Pada PT Adaro Energy, PT Indika Energy, dan PT Harum Energy Tahun 2019 - 2021 - Fahrizal Akhmad Zein; Farrel Daffa Setiawan; Rendy Ardiansyah (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study aims to analyze the time series and cross section of financial performance comparisons that occurred at PT Adaro Energy, PT Indika Energy, and PT Harum Energy in 2019-2021. The research method used is descriptive qualitative by taking data sources obtained from the corporate websites of PT Adaro Energy Tbk, PT Harum Energy, PT Indika Energy Tbk and the website idx.com. The results found that PT HRUM is a company with the best prospects seen from various comparisons. While PT INDY is considered to have the best management control compared to the other two companies. PT ADRO has no problems that need to be underlined, they just need to improve a little.